Decoding the Electronic Image. - DRYANSKY, LARISA (Afterimage, 2023)
The article explores Woody Vasulka's dedication to didactics in video and digital art, focusing on two instructional articles published in 1975 and 1978. Topics include into Vasulka's experiments with the analog Rutt/Etra Scan Processor, showcasing his use of waveform generation to create abstract constructions and the illusion of three-dimensionality; and discusses Vasulka's foray into the digital realm with the Digital Image Articulator.